2015
DOI: 10.1002/bit.25661
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modelling of high biomass density cultivation and biohydrogen production in different scales of flat plate photobioreactors

Abstract: This paper investigates the scaling‐up of cyanobacterial biomass cultivation and biohydrogen production from laboratory to industrial scale. Two main aspects are investigated and presented, which to the best of our knowledge have never been addressed, namely the construction of an accurate dynamic model to simulate cyanobacterial photo‐heterotrophic growth and biohydrogen production and the prediction of the maximum biomass and hydrogen production in different scales of photobioreactors. To achieve the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…Although previous research demonstrated that bubble scattering may play an important role causing light attenuation in a low biomass concentration culture [32], [50], its zero value calculated through the current parameter estimation procedure indicates that its effect on light attenuation is negligible compared to that of cell absorption in the current study. This conclusion is also consistent with recent studies which found that light attenuation is predominantly led by cell absorption instead of bubble scattering for cyanobacterial biohydrogen and C-phycocyanin production [37], [51].…”
Section: Parameters In H Pluvialis Zy-18 Modelssupporting
confidence: 93%
“…Although previous research demonstrated that bubble scattering may play an important role causing light attenuation in a low biomass concentration culture [32], [50], its zero value calculated through the current parameter estimation procedure indicates that its effect on light attenuation is negligible compared to that of cell absorption in the current study. This conclusion is also consistent with recent studies which found that light attenuation is predominantly led by cell absorption instead of bubble scattering for cyanobacterial biohydrogen and C-phycocyanin production [37], [51].…”
Section: Parameters In H Pluvialis Zy-18 Modelssupporting
confidence: 93%
“…Along with open photobioreactors (Apel and Weuster-Botz, 2015), many different closed reactor types with a diversity of reactor geometries and characteristics are proposed for microalgae cultivation (Borowitzka, 1999;Lee, 2001;Tang et al, 2012;Ugwu et al, 2008). Thus, bioreactors such as bubble column reactors (B echet et al, 2013), flat-plate bioreactors (Zhang et al, 2015), or tubular reactors (Camacho Rubio et al, 1999;Huang and Rorrer, 2002;Rorrer and Mullikin, 1999) have been explored. Furthermore, novel photobioreactor configurations such as an oscillatory baffled reactor (Abbott et al, 2015) or a Taylor vortex reactor (Kong et al, 2013) were recently developed for an improved microalgal biomass production.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon uptake rate of cyanobacterial fermentations is generally high during the initial growth rate, but decreases at steady state when biomass concentrations of approx. 3 g CDW /l are reached ( Zhang et al, 2015 ). The decrease in carbon uptake is probably caused by shadow-casting of cells at higher biomass concentrations resulting in photon-limited growth.…”
Section: Discussionmentioning
confidence: 99%